Social media use and mental health during the COVID-19 pandemic in young adults: a meta-analysis of 14 cross-sectional studies - Youngrong Lee; Ye Jin Jeon; Sunghyuk Kang; Jae Il Shin; Young-Chul Jung; Sun Jae Jung (BMC, 2022)
Abstract Background Public isolated due to the early quarantine regarding coronavirus disease 2019 (COVID-19) increasingly used more social media platforms. Contradictory claims regarding the effect of social media use on mental health needs to be resolved. The purpose of the study was to summarise the association between the time spent on social media platform during the COVID-19 quarantine and mental health outcomes (i.e., anxiety and depression). Methods Studies were screened from the PubMed, Embase, and Cochrane Library databases. Regarding eligibility criteria, studies conducted after the declaration of the pandemic, studies that measured mental health symptoms with validated tools, and studies that presented quantitative results were eligible. The studies after retrieval evaluated the association between time spent on social media platform and mental health outcomes (i.e. anxiety and depression). The pooled estimates of retrieved studies were summarised in odds ratios (ORs). Data analyses included a random-effect model and an assessment of inter-study heterogeneity. Quality assessment was conducted by two independent researchers using the Risk of Bias Assessment Tool for Nonrandomized Studies (RoBANS). This meta-analysis review was registered in PROSPERO ( https://www.crd.york.ac.uk/PROSPERO/ , registration No CRD42021260223, 15 June 2021). Results Fourteen studies were included. The increase in the time spent using social media platforms were associated with anxiety symptoms in overall studies (pooled OR = 1.55, 95% CI: 1.30-1.85), and the heterogeneity between studies was mild (I2 = 26.77%). Similarly, the increase in social media use time was also associated with depressive symptoms (pooled OR = 1.43, 95% CI: 1.30-1.85), and the heterogeneity between studies was moderate (I2 = 67.16%). For sensitivity analysis, the results of analysis including only the "High quality" studies after quality assessment were similar to those of the overall study with low heterogeneity (anxiety: pooled OR = 1.45, 95% CI: 1.21-1.96, I2 = 0.00%; depression: pooled OR = 1.42, 95% CI: 0.69-2.90, I2 = 0.00%). Conclusions The analysis demonstrated that the excessive time spent on social media platform was associated with a greater likelihood of having symptoms of anxiety and depression.